A New Perspective on Hydrogen Chloride Scavenging at High Temperatures for Reducing the Smoke Acidity of PVC in Fires—III: EN 60754-2 and the Species in Solution Affecting pH and Conductivity - Iacopo Bassi; Claudia Bandinelli; Francesca Delchiaro; Gianluca Sarti (Fire)
In the European Union, Regulation (EU) No 305/2011, in force since 2017 as CPR, requires the classification of cables permanently installed in buildings for reaction to fire, smoke, flaming droplets, and acidity. The latter is an additional classification evaluated through EN 60754-2, involving pH and conductivity measurements. Acidity is the weak point of a PVC cable due to the release of HCl during the combustion. Low-smoke acidity compounds, containing potent acid scavengers at high temperatures, are developed to reduce the acidity of the smoke. In order to design proper HCl scavengers to be used in PVC low-smoke acidity compounds, it becomes essential to evaluate the main actors affecting acidity and conductivity. In this paper, different cable PVC compounds were tested carrying out EN 60754-2 at different temperatures and temperature regimes: measurements of pH and conductivity were compared with ions’ concentration determined by ion chromatography, according to ISO 10304-1 and ISO 14911 for anions and cations, and inductively coupled plasma–optical emission spectrometry, according to ISO 11885. The conclusive results emphasize that HCl from PVC compounds’ thermal decomposition is the primary driver of pH and conductivity, and the contribution from the evaporation and or decomposition of additives and by-products from combustion is found to be negligible in most of the tested PVC compounds for cables. The findings highlight the effectiveness of ion chromatography and inductively coupled plasma–optical emission spectrometry as powerful analytical tools for developing efficient acid scavengers capable of maintaining performance at elevated temperatures. A further outcome regards the experimental demonstration of the limits and incongruencies of EN 60754-2 as an instrument for assessing the additional classification for acidity for cables. Finally, a statistical method to understand through pH and conductivity measurements if the scavenging mechanism acts in the condensed phase is presented.